Humoral response to neurofilaments and dipeptide repeats in ALS progression. Issue 9 (27th July 2021) - Puentes, Fabiola; Lombardi, Vittoria; Lu, Ching‐Hua; Yildiz, Ozlem; Fratta, Pietro; Isaacs, Adrian; Bobeva, Yoana; Wuu, Joanne; ,; ,; Benatar, Michael; Malaspina, Andrea
Abstract: Objective: To appraise the utility as biomarkers of blood antibodies and immune complexes to neurofilaments and dipeptide repeat proteins, the products of translation of the most common genetic mutation in amyotrophic lateral sclerosis (ALS). Methods: Antibodies and immune complexes against neurofilament light, medium, heavy chains as well as poly‐(GP)‐(GR) dipeptide repeats were measured in blood samples from the ALS Biomarkers ( n = 107) and the phenotype–genotype biomarker ( n = 129) studies and in 140 healthy controls. Target analyte levels were studied longitudinally in 37 ALS cases. Participants were stratified according to the rate of disease progression estimated before and after baseline and C9orf72 genetic status. Survival and longitudinal analyses were undertaken with reference to matched neurofilament protein expression. Results: Compared to healthy controls, total neurofilament proteins and antibodies, neurofilament light immune complexes ( p < 0.0001), and neurofilament heavy antibodies ( p = 0.0061) were significantly elevated in ALS, patients with faster progressing disease ( p < 0.0001) and in ALS cases with a C9orf72 mutation ( p < 0.0003). Blood neurofilament light protein discriminated better ALS from healthy controls (AUC: 0.92; p < 0.0001) and faster from slower progressing ALS (AUC: 0.86; p < 0.0001) compared to heavy‐chain antibodies and light‐chain immune complexes (AUC: 0.79; p < 0.0001 and AUC: 0.74; p < 0.0001). Lower neurofilament heavy antibodies were associated with longer survival (Log‐rank Chi‐square: 7.39; p = 0.0065). Increasing levels of antibodies and immune complexes between time points were observed in faster progressing ALS. Conclusions: We report a distinctive humoral response characterized by raising antibodies against neurofilaments and dipeptide repeats in faster progressing and C9orf72 genetic mutation carriers ALS patients. We confirm the significance of plasma neurofilament proteins in the clinical stratification of ALS.